Upaya Pemenuhan Standar Kehidupan Yang Layak Bagi Narapidana Lansia Di Lembaga Pemasyarakatan Kelas II A Jambi: English - Prasetheo Nuari, Kumdhan (Jurnal Panorama Hukum, 2021)
This study aims to find out how the effort to fulfill a decent standard of living for elderly inmates (elderly) in the Class II A Jambi Penitentiary is and what obstacles are faced by the correctional institution in the effort to fulfill this process. In achieving these goals, the data collection techniques used are direct field observations, case studies and reinforced by interviews with informants. The data obtained from the results of this study were processed through a qualitative approach using juridical-empirical analysis to find out how the process of fulfilling a decent standard of living for elderly prisoners in terms of eating, drinking, health, sleeping accommodation and sleeping equipment is. The results of this study indicate that: 1. The process of fulfilling the rights of elderly prisoners in the Class II A Jambi Penitentiary is quite feasible. However, the elderly inmates complained more about the residential rooms that were not separated. In the process of implementing the proper fulfillment of the rights of elderly prisoners in terms of accommodation of residential rooms, it has not been in accordance with the guidelines of the Minister of Law and Human Rights Number 32 of 2018 concerning Treatment for Elderly Detainees and Inmates. 2. Obstacles encountered in the implementation of proper fulfillment of the rights of elderly prisoners in the Class II A Jambi prison include the low budget so that it has an impact on the quality of facilities and infrastructure that are not maintained and inadequate in supporting the special treatment given to the elderly prisoners. The unavailability of sufficient room for elderly inmates to rest properly, due to overcrowded which has almost reached 500%, has not been optimal in the implementation of fulfilling a decent standard of living for elderly inmates.